The Relationship Between Nutritional Status with Malondialdehyde (MDA) and Vitamin D Level - Anastasya, Karina Shasri; Faradilla, Meutia Atika; Satyasari, Daniella; Larasari, Andira (The Avicenna Medical Journal, 2025)
Background: Nutritional status has been found to be correlated with malondialdehyde (MDA) profiles in the blood. MDA is a marker of oxidative stress in the body and is the final product of lipid peroxidation chain reactions. The long-term undernutrition and excess status will be closely related to metabolic disorders and degenerative diseases. Street cleaning staff are often exposed to free radicals that will improve lipid peroxidation, which will also break down into MDA. Vitamin D serum levels have an inverse correlation with adipose tissue mass, where the higher the BMI and body fat mass of a person, the lower the levels of vitamin D serum. The purpose of this study was to determine the relationship of nutritional status with MDA and vitamin D levels in the blood. Methods: This research will be conducted from July 2024 to February 2025, using a cross-sectional design at the Faculty of Medicine, Trisakti University, with the target population being the street cleaning staff in Jakarta. The samples were taken by consecutive sampling for all street cleaning staff who met the inclusion and exclusion criteria, with a total of 76 samples. Results: The results showed that there was no significant relationship between nutritional status with MDA and vitamin D, but there was a significant relationship between vitamin D and MDA (r=0.190; p=0.047). Conclusion: Higher BMI is associated with a relative reduction in muscle mass percentage and a substantial increase in visceral adiposity, irrespective of sex. These findings suggest that BMI alone may not adequately represent body composition or metabolic risk and support the routine use of body composition assessment as a complementary tool in clinical obesity evaluation. Keywords: Nutritional status, MDA, vitamin D